Serratia plymuthica MBSA-MJ1 Increases Shoot Growth and Tissue Nutrient Concentration in Containerized Ornamentals Grown Under Low-Nutrient Conditions - Nordstedt, Nathan P.; Jones, Michelle L. (Frontiers in Microbiology, 2021)
High fertilizer rates are often applied to horticulture crop production systems to produce high quality crops with minimal time in production. Much of the nutrients applied in fertilizers are not taken up by the plant and are leached out of the containers during regular irrigation. The application of plant growth promoting rhizobacteria (PGPR) can increase the availability and uptake of essential nutrients by plants, thereby reducing nutrient leaching and environmental contamination. Identification of PGPR can contribute to the formulation of biostimulant products for use in commercial greenhouse production. Here, we have identified Serratia plymuthica MBSA-MJ1 as a PGPR that can promote the growth of containerized horticulture crops grown with low-fertilizer inputs. MBSA-MJ1 was applied weekly as a media drench to Petunia × hybrida (petunia), Impatiens walleriana (impatiens), and Viola × wittrockiana (pansy). Plant growth, quality, and tissue nutrient concentration were evaluated eight weeks after transplant. Application of MBSA-MJ1 increased the shoot biomass of all three species and increased the flower number of impatiens. Bacteria application also increased the concentration of certain essential nutrients in the shoots of different plant species. In vitro and genomic characterization identified multiple putative mechanisms that are likely contributing to the strain’s ability to increase the availability and uptake of these nutrients by plants. This work provides insight into the interconnectedness of beneficial PGPR mechanisms and how these bacteria can be utilized as potential biostimulants for sustainable crop production with reduced chemical fertilizer inputs.